Negative sanctions and the EU's external migration policy: "Less for less" not fit for purpose - David Kipp; Nadine Knapp; Amrei Meier (Stiftung Wissenschaft und Politik (SWP), 2020)
The European Commission has announced plans to present a new 'Pact on Migration and Asylum' during the German EU Council Presidency. It is expected to provide impetus for the long-overdue reform of the Common European Asylum System, for the strengthening of the EU's external borders, and for improved cooperation on migration policy with third countries. Many EU states see the latter as being particularly urgent in order to persuade countries of origin to readmit citizens who are obliged to leave the EU. In addition to positive incentives, sanctions against third countries that are unwilling to cooperate are increasingly being discussed. Although sanctions can have a short-term effect, they do not appear to be sustainable and can jeopardise more far-reaching goals of European foreign and development policy. Therefore, during its Presidency, Germany should instead advocate for migration policy instruments that aim to achieve a long-term and fair balance of interests between the EU and third countries.
Keywords: 320